PERAN PEMUDA DALAM PENINGKATAN PENDAPATAN KELUARGA (STUDI KASUS PEMBUDIDAYA RUMPUT LAUT Eucheuma Cottoni DI DESA ALLANG ASAUDE KABUPATEN SERAM BAGIAN BARAT) - Michael Gilbert Duganata; Johanis Hiariey; Yoisye Lopulalan (Universitas Pattimura, 2021)
Development in the marine and fisheries sector is supported by opportunities for resource utilization and management that are distributed in three Fishery Management Areas (WPP), namely the Banda Sea (WPP 714), Seram Sea and Tomini Bay (WPP 715), Arafura Sea and Timor Sea (WPP 718). The fishery sector in Maluku creates opportunities for commercial businesses in the industrial sector, both in cultivation, fishing and processing, including small and large businesses. A fishery commodity that has good prospects and benefits fishing communities is seaweed cultivation. The West Seram District Government in its development policy has placed the Eucheuma cottonii seaweed commodity as a leading commodity to be developed. Youth roles are needed in cultivation activities, so it can be said that youth tend to place economic interests above other interests in determining how and where they should play a role in development. Share factor analysis is used to measure the contribution of youth income to family income and total family income is calculated by adding up youth income and family income.